How multiple threats to safety affects quality of life for picky eating adults: A new explanatory model. (1st February 2023) - Fox, Gemma; Coulthard, Helen; Williamson, Iain; Aldridge, Victoria
Abstract: Picky eating describes a pattern of eating characterised by a narrow dietary range with rejection of both novel and familiar foods. Research has suggested that picky eating in adulthood is associated with several negative psychosocial outcomes including impaired quality of life. This research aimed to build and test a model explaining the relationship between picky eating and quality of life. 230 participants were recruited via online support forums for picky eating, and an undergraduate research participation scheme. Participants completed self-report measures of picky eating, sensory sensitivity, disgust, anxiety, fear of negative evaluation and eating related quality of life. Regression analysis indicated that picky eating, disgust sensitivity, anxiety, and fear of negative evaluation were all associated with impaired eating-related quality of life. A theoretical model was then devised which aimed to explain the interactions between these factors, and Path Analysis indicated that this model was a good fit for the data. This Safety in Picky Eating and Quality of life (SPEQ) model suggests that threat perception and the drive for safety underlies the relationship between picky eating and impaired quality of life. The SPEQ model provides a preliminary basis for understanding how picky eating impacts quality of life in adulthood.